Raum und Zeit zwischen Sichtbarem und Vorstellbarem – Multimodales space- und time-making in der Tourismuskommunikation - Messner, Monika (Linguistik Online, 2026)
This article examines the multimodal representation and coding of spatiality and temporality in tourism discourse. Tourism communication is understood as spatial communication in which a geographical or topographical space is transported into a touristic sight; and as temporal communication in which touristic time is represented as extraordinary and as counterpart to ordinary everyday time. Space and time are very closely linked with each other and enter cohesive and coherent relationships to fulfill the object of destination promotion. For this, verbal, visual and typographical means are efficiently used and combined. Methodologically, the study is based on multimodal semiotic discourse analysis and visual linguistics. Using selected printed and digital examples from different destinations, the article investigates how space and time are contextualized and interwoven, specifically exploring which spatial concepts enable an understanding of temporality and which temporal markers are influenced by spatiality. Furthermore, the extent to which the medium (print versus digital) influences this relationship will be included into the analysis.